IT GOVERNANCE: MEASURE CAPABILITY LEVEL USING COBIT 5 FRAMEWORK - Noor Mutia; Renny Nur'ainy (Universitas Gunadarma, 2020)
The measurement of IT Governance capability level becomes useful for companies in order to reduce and avoid the mistake and losses in IT management. This research aims to measure the capability level of IT Governance in Oil & Gas Company listed in Indonesia, in occasion at PT Energi Mega Persada Tbk (EMP), and support the IT governance that has not reached the EMP’s target. The data engaged directly from respondents achieved from the results of questionnaires, interviews and observations. COBIT 5 Framework developed to measure the capability level of process by using Process Assessment Model (PAM). The result found that the capability level of IT Governance measurement of 37 IT processes for all domains in EMP presently at level 3,3 or established level. It means that IT Governance based on COBIT 5 in EMP has been commonly documented, communicated and implemented by default and has standardized. This research is likely to assist company in realize the capability level of IT Governance presently matched to the target that the company wants to reach. In order to the enhancements can conduct to make IT Governance more effective, efficient, and able to support the achievement of company goals.